Seorang Wanita Berusia 27 Tahun dengan Tuberkulosis Genitourinari: Masalah Diagnosis di Daerah Pedesaan Indonesia - Laporan Kasus: Laporan Kasus - Asali, Teresa; Setiady, Feddy; Putra, Agung Ambara; Salim, Harina (Cermin Dunia Kedokteran, 2026)
Introduction: Genitourinary tuberculosis (TB) is one of the most common forms of extrapulmonary TB, yet it is often misdiagnosed due to its nonspecific symptoms and very often mimic recurrent urinary tract infections. Case: A 27-year-old woman was referred to the hospital with complaints of frequent and painful urination for the past six months, along with intermittent fever and occasional cough.She had received multiple courses of antibiotics, but her symptoms did not resolve. Laboratory investigations, including urine microscopy, LAM antigen, and Xpert MTB/RIF, revealed Mycobacterium tuberculosis in the urine sample. A chest x-ray and sputum acid fast bacilli (AFB) examination indicated pulmonary tuberculosis. The patient was treated with standard anti-tuberculosis drugs for 6 months, resulting in clinical improvement. Discussion: Diagnosing genitourinary TB is challenging due to its nonspecific presentation and the limited sensitivity of routine urine microscopy. While Xpert MTB/RIF offers higher accuracy, its availability is restricted in many settings. LAM testing shows usefulness in HIV-associated TB, but its role in non-HIV genitourinary TB is still uncertain. Improved, accessible diagnostic strategies are needed for earlier detection. Conclusion: Genitourinary TB remains challenging to diagnose, particularly in rural areas with limited access to advanced diagnostics. A careful medical history, repeat urinalysis, and simple tests such as urine smear microscopy, LAM, and MTB/RIF can aid early detection. Early diagnosis is essential to prevent complications such as end-stage kidney failure.